Giant cell temporal arteritis: a clinicopathological study with emphasis on unnecessary biopsy - Alkatan, Hind M.; AlMana, Fawziah; Maktabi, Azza M. Y. (Frontiers in Ophthalmology, 2023)
Temporal artery (TA) biopsy is commonly used for the diagnosis of giant cell arteritis (GCA). However, a positive biopsy is no longer mandatory for diagnosis. This study aims to correlate the histopathological findings of TA biopsies in suspected cases of GCA to the clinical presentation in an ophthalmic tertiary eye care center to draw useful conclusions and advocate the possible implementation of guidelines for TA biopsy. Data was collected from patients' medical records including, demographics, clinical data, and histopathological findings and diagnosis. The 2022 American College of Rheumatology/ European Alliance of Associations for Rheumatology (ACR/EULAR) criteria have been used and partially adopted as a guide to compare the variables between TA biopsy-positive and negative groups as well as the TA biopsy-positive group and the group of patients with TA biopsy showing atherosclerosis. Out of the total 35 patients who underwent a TA biopsy, 22.9% of patients had histopathological findings consistent with GCA and 42.9% had TA atherosclerotic changes, while the remaining 34.3% had histologically unremarkable TAs In the, the mean diagnostic clinical score used in our study was higher (7.5 ± 2.33) in the GCApositive group when compared to the other groups with statistical significance (mean of 4.85 ± 2.01 in patients with overall GCA-negative biopsies and 5.13 ± 2.10 in the group with atherosclerosis). Other three clinical variables that were found to be statistically significant in the GCA biopsypositive group were scalp tenderness, jaw claudication, and optic nerve pallor. In addition, the mean age (71± 8.4 years) and the female predominance of GCA in our group of patients with positive TA biopsy (62.5%) was similar to other reports. The incorporation of increased clinically focused assessments and algorithms, with the aid of the ACR/EULAR criteria, may decrease the frequency of TA biopsies that carries unnecessary cost and risk of procedure-related morbidity. We also highly recommend applying the cut-off age (≥ 50 years) as an initial step.